Is there an association between aspects of the metabolic syndrome and overactive bladder? A prospective cohort study in women with lower urinary tract symptoms. (October 2017) - Zacche, M.M.; Giarenis, I.; Thiagamoorthy, G.; Robinson, D.; Cardozo, L.
Abstract: Objective: The aim of our study was to determine whether there is a link between aspects of the metabolic syndrome (MetS) and overactive bladder (OAB) in women with lower urinary tract symptoms (LUTS). Study design: A single-centre prospective study. We evaluated a cohort of consecutive women with LUTS attending a tertiary referral urodynamic clinic from October 2012 to January 2015. Obesity, diabetes, hypertension and dyslipidaemia were used as markers of MetS. OAB and detrusor overactivity (DO) were defined according to the International Urogynaecological Association/International Continence Society terminology. Results: Eight hundred and forty women were enrolled. Three hundred and eight (36.6%) had normal weight, 260 (31%) were overweight and 272 (32.4%) obese. We identified 168 women (20%) with hypertension, 64 (7.6%) with diabetes mellitus, and 98 (11.7%) with dyslipidaemia. Seven hundred and four (83.8%) women were diagnosed symptomatically with OAB and 305 (36.3%) were diagnosed urodynamically with DO. Obesity (p < 0.001) was the only independent predictor for OAB (OR 1.09, 95% CI 1.05–1.13) and DO (OR 1.06, 95% CI 1.03–1.08), respectively. Conclusion: Our study demonstrates a correlation between obesity and OAB/DO in female patients. However, other components of MetS do not appear to be associated with either OAB and DO. Weight reduction should be strongly recommended in women with OAB.